Efficacy and safety of Shexiang Baoxin Pill for stable coronary artery disease: A systematic review and meta-analysis of 42 randomized controlled trials - Wei, Jingjing; Ma, Teng; Zhou, Cheng; Hao, Pengle; Li, Bin; Wang, Xinlu; Yu, Rui; Zhu, Mingjun; Wang, Yongxia (Frontiers in Pharmacology, 2022)
Objective: Patients with stable coronary artery disease (SCAD) still have a higher risk of adverse cardiovascular events. Shexiang Baoxin Pill (SBP) is widely used as a complementary and alternative treatment for SCAD. This study aimed to further verify the therapeutic effect and safety of SBP on SCAD. Methods: Seven databases were involved in this meta-analysis as of June 1, 2022. Data was collected from all the randomized controlled trials (RCTs) of the combination of SBP and conventional western medicine (CWM) in treating SCAD which was conducted by two independent authors. Risk of bias was assessed using the Cochrane risk-of-bias 2.0 (RoB2.0) tool, and the meta-analysis was accomplished with Review Manager 5.3. Furthermore, the Grading of Recommendations Assessment, Development and Evaluation (GRADE) profiler 3.2.2 software was selected to grade the current evidence in our findings. Results: 42 articles, involving 6694 patients were screened among all the 1374 records in the analysis. The results demonstrated that the combination therapy was more efficient than CWM alone in lowering the incidence of major adverse cardiovascular events (MACE, RR=0.50, 95% CI: 0.37 to 0.68, P<0.00001) and ameliorating the effective rate of angina symptom improvement (RR=1.23, 95% CI: 1.19 to 1.28, P<0.00001), the effective rate of electrocardiogram improvement (RR=1.34, 95% CI: 1.26 to 1.43, P<0.00001), the frequency of angina pectoris (MD=-2.83, 95% CI: -3.62 to -2.05, P<0.00001), and the duration of angina pectoris (MD=-1.32, 95% CI: -2.04 to -0.61, P=0.0003). We also found that, after SBP treatment, a more positive blood lipid level and left ventricular ejection fraction without the increase in adverse cases were calculated in our meta-analysis. What’s more, Subgroup analysis indicated that treatment duration may be the source of heterogeneity. The certainty of the evidence for MACE, and electrocardiogram improvement exhibited moderate certainty, and the certainty of the evidence for the remaining outcomes was judged as low certainty. The trial sequential analysis further affirmed the clinical efficacy of SBP. Conclusion: The available evidence indicates that SBP may be an effective therapeutic option in patients with SCAD. However, considering the inferior quality and inconsistent results in the included trials, further rigorous RCTs are required.